Phenolic compounds and antioxidant activity in Cucurbita ficifolia fruits, an underrated fruit - Moreno-Quiroga, G.; Alba-Jiménez, J.E.; Aquino-Bolaños, E. N.; Chávez-Servia, J. L. (Frontiers in Nutrition, 2023)
The fruits and seeds of Cucurbita ficifolia Bouché are sources of minerals, vitamins, and functional compounds with nutraceutical and preventive potential against cardiovascular diseases and diseases derived from eating disorders. C. ficifolia is native from Mesoamerica and is currently cultivated in temperate zones from Mexico to South America and Asia. This study evaluated the fruit mesocarps of C. ficifolia for physicochemical parameters, antioxidant activity, and phenolic compound contents in a collection of farmers’ landraces. Germplasm is cultivated by traditional farmers in the temperate zones of two municipalities from Oaxaca, Mexico. The results show that the content of soluble solid contents (SSC), pH, total sugars (TS) and flavonoids are influenced by the fruit geographical origin (municipalities) and implicitly by their agroecological cultivation conditions (Huamelúlpam: SSC = 6.22 °Brix, pH = 5.44, TS = 0.52 mg G g-1, flavonoids = 1.24 mg CE g-1; Yanhuitlán: SSC = 6.69, pH = 5.33, TS = 0.55, flavonoids = 1.30). Among populations preserved by traditional farmers, significant differences and wide variability were found for all parameters evaluated (Huamelúlpam: SSC = 4.9 -7.3, pH = 5.5 - 5.8, TS = 0.4 - 0.7, protein = 5.8 - 11.4, polyphenols = 1.9 - 4.8, flavonoids = 1.0 - 1.5, DPPH = 4.3 - 10.6, and FRAP = 4.8 - 11.8; Yanhuitlán: SSC = 4.3 - 8.9, pH = 4.8 - 5.6, TS = 0.4 - 0.7, protein = 5.0 - 15.3, polyphenols = 1.9 - 4.9, flavonoids = 0.8 - 1.9, DPPH = 5.3 - 10.5, and FRAP = 4.5 - 12.6). Eight compounds were identified by UPLC‒MS: L-phenylalanine, an amino acid that is regularly associated with proteins; vanillin, a phenolic aldehyde with its functional groups including aldehyde, hydroxyl, and ether; and six phenolic acids: 4-hydroxybenzoic acid, 4-hydroxyphenylacetic acid, vanillic acid, 4-coumaric acid, ferulic acid, and salicylic acid, all with potential health effects. The C. ficifolia fruit mesocarp has bioactive compounds with high antioxidant activity with the potential to both improve diet and to obtain other benefits against nontransmissible diseases derived from food and its associated risk factors.